Effectiveness of Emotion Regulation Therapy on the Resilience of Caregivers of Schizophrenia Patients in Aceh: A Quasy-Experimental Study - Khalida, Hayyuni; Syarifah, Rauzatul Jannah; Marthoenis (LPPM Universitas Prima Nusantara Bukittinggi, 2025)
Schizophrenia is a chronic mental disorder that requires long-term care, which puts caregivers at risk of emotional burdens that can decrease their level of resilience. Families, as caregivers, play an important role in patient care and need to possess strong emotional endurance. Emotion Regulation Therapy is an intervention aimed at improving individuals’ ability to manage emotions adaptively to enhance resilience. This study aims to determine the effect of emotion regulation therapy on increasing the resilience of caregivers who care for patients with schizophrenia in Aceh. The study used a quasi-experimental design with a one-group pre-post-test approach. The sample consisted of 33 caregivers selected through purposive sampling and was given emotion regulation therapy over seven sessions. The instruments used in this study were a demographic data sheet to obtain respondent characteristics and the Connor-Davidson Resilience Scale (CD-RISC) questionnaire to measure resilience levels. The Wilcoxon Signed-Rank Test results showed a significant effect of emotion regulation therapy on increasing caregiver resilience, with a Z value = -5.205 and p < 0.001. The results indicated that before the intervention, the majority of respondents (51.5%) were in the low resilience category. After the intervention, there was a significant increase, with 84.8% of respondents categorized as having high resilience. Additionally, the average resilience score increased from 49.00 to 73.15. Based on these findings, emotion regulation therapy has been shown to be effective in increasing the resilience of caregivers caring for patients with schizophrenia. These results indicate that this intervention can be used as a relevant strategy to help caregivers deal with long-term emotional stress.